Transaksi Jual Beli dan Fiqih Media Sosial - Nur Annisa Tri Handayani; Ahmadih Rojalih Jawab (CV. Ulil Albab Corp, 2023)
In the modern digital era, the phenomenon of buying and selling via social media has experienced rapid development. Transactions using online media from the point of view of buying and selling jurisprudence are permitted in Islam in accordance with the jurisprudence rules